2010
DOI: 10.1016/j.bmcl.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a Eu-DTPA-PEGO-MSH(4) derivative for evaluation of binding of multivalent molecules to melanocortin receptors

Abstract: A labeled variant of MSH(4), a tetrapeptide that binds to the human melanocortin 4 receptor (hMC4R) with low µM affinity, was prepared by solid phase synthesis methods, purified, and characterized. The labeled ligand, Eu-DTPA-PEGO-His-DPhe-Arg-Trp-NH 2 , exhibited a K d for hMC4R of 9.1±1.4 µM, approximately 10-fold lower affinity than the parental ligand. The labeled MSH(4) derivative was employed in a competitive binding assay to characterize the interactions of hMC4R with monovalent and divalent MSH(4) cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The K i for the monovalent control compound 14 was 1.4 times the value for the parental ligand, indicating that attachment of the triazole-containing “spacer” to the N-terminus of MSH(4) has a modest detrimental effect on ligand binding to hMC4R. In keeping with prior results obtained with the squalene-derived monovalent and divalent MSH(4) constructs 1 and 2 ,11 multimer 16e was shown to be nearly as potent as MSH(4), but not more so, in Assay A. This result suggests monovalent binding of 16e at available hMC4R.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The K i for the monovalent control compound 14 was 1.4 times the value for the parental ligand, indicating that attachment of the triazole-containing “spacer” to the N-terminus of MSH(4) has a modest detrimental effect on ligand binding to hMC4R. In keeping with prior results obtained with the squalene-derived monovalent and divalent MSH(4) constructs 1 and 2 ,11 multimer 16e was shown to be nearly as potent as MSH(4), but not more so, in Assay A. This result suggests monovalent binding of 16e at available hMC4R.…”
Section: Discussionsupporting
confidence: 77%
“…Hek293 cells overexpressing hMC4R were used to assess ligand binding22 using two previously described europium-based competitive binding assays 11,23. Assay A23a employed Eu-DTPA-NDP-α-MSH-NH 2 ( 17 ) as the labeled probe, and Assay B11 employed Eu-DTPA-PEGO-MSH(4)-NH 2 ( 18 ) as the labeled probe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While MALDI-TOF analysis was reasonably consistent with statistical attachment of ligands in the case of 14c , the mass spectra for 14d and 14e suggested that ligand attachment was not statistical (see Figure 3 and Figures S4–S6 in the Supplementary Data). MALDI-TOF analysis of a 1:1 mixture of monovalent and divalent MSH4 constructs on a squalene scaffold 17,27 demonstrated a highly attenuated sensitivity for detection of the divalent construct. Thus, MALDI-TOF analysis of multimers 14c–14e is qualitative, with actual distributions of MSH4 ligands somewhere between the MALDI-TOF limit of analysis and the expected statistical distributions.…”
Section: Discussionmentioning
confidence: 99%
“…22 In our prior work, the azide N 3 (CH 2 ) 5 (C=O)-His- d Phe-Arg-Trp-NH 2 ( 1 , Scheme 1) was attached to a linear scaffold (e.g., 2 ) bearing terminal alkyne groups using the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC), 2326 producing triazole-containing multivalent constructs (e.g., 3 ). 18 The abilities of 3 and of similar monovalent and multivalent constructs based on MSH4 to bind to MC4R were tested in competitive binding assays against probes 4 11 and 5 27 using Hek293 cells engineered to overexpress this receptor. Probe 4 is based on the superpotent ligand Ser-Tyr-Ser-Nle-Glu-His- d Phe-Arg-Trp-Gly-Lys-Pro-Val-NH 2 (NDP-α-MSH), 28,29 while the probe 5 is based on MSH4.…”
Section: Introductionmentioning
confidence: 99%